Barriers to Effective Communication between Patients, Relatives, and Health Care Professionals in the Era of COVID-19 Pandemic at Public Hospitals in Limpopo Province - Ndidzulafhi Selina Raliphaswa; Dorah Ursula Ramathuba; Takalani Rhodah Luhalima; Seani Adrinah Mulondo; Thivhulawi Malwela; Azwidihwi Rose Tshililo; Julia Langanani Mafumo; Maria Sonto Maputle; Mary Maluleke; Takalani Ellen Mbedzi; Hilda Nwamuhohova Shilubane; Nthomeni Dorah Ndou; et al. (MDPI AG, 2023)
Background: Effective communication between health care professionals, admitted patients, and their families is crucial to improving the health care outcomes and patient satisfaction. Hence, barriers to effective communication cause a lot of confusion, frustration, and misunderstanding. The study aimed to identify the perceived barriers to effective communication between patients, their families, and health care professionals during the COVID-19 pandemic in public hospitals in Limpopo Province. The study was conducted in rural areas of Vhembe District, Limpopo Province. Methodology: A qualitative exploratory descriptive method was adopted to explore and describe the barriers of effective communication among patients, relatives, and health care professionals during the COVID-19 pandemic in public hospitals in the Vhembe District. Eleven (11) participants were purposively selected. Unstructured in-depth individual interviews were used to collect data and analyzed using thematic analysis following Tesch's eight steps. Results: The study findings revealed that there was ineffective communication by health care professionals. This was discussed under three themes that emerged: poor communication of diagnosis and prognosis and treatment outcomes; lack of accurate knowledge regarding the virus morphology, variant, and treatment protocols; and the inconsistencies in the dissemination of COVID-19 protocols. Conclusions: Full communication benefits both patients, relatives, and health care professionals as knowledge and understanding are enhanced through communication. Therefore, health care professionals should provide the patients and their relatives with full information about the disease and the visitation protocols to be followed. The study contribution was to explore barriers to effective communication to the patients and relatives by the health care professionals.